1974
DOI: 10.1128/aac.5.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Pactamycin and Sparsomycin on Mycoplasma -Induced Lethal Toxicity of Mice

Abstract: Pactamycin and sparsomycin, antitumor drugs which act synergistically with endotoxins, also potentiate the lethal toxicity of mice by Mycoplasma fermentans, strain K10. Sparsomycin (50 ug/20 g mouse, injected intraperitoneally 1 h after various doses of M. fermentans) exerted a minimal degree of synergism with few extra deaths, but with prolonged appearance of nonlethal disease. Pactamycin (75 gg in the same protocol) increased susceptibility to Mycoplasma-induced lethal toxicity approximately 1,000-fold. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
1993
1993

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Mycoplasma. The origin of M. fermentans, strain K10, and methods of cultivation and enumeration have been described previously (7,9,10). Cultures were grown to peak log phase in 500to 1,000-ml lots and were collected by centrifugation at 12,000 x g for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Mycoplasma. The origin of M. fermentans, strain K10, and methods of cultivation and enumeration have been described previously (7,9,10). Cultures were grown to peak log phase in 500to 1,000-ml lots and were collected by centrifugation at 12,000 x g for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that antitumor compounds that inhibit deoxyribonucleic acid synthesis (e.g., actinomycin D, sparsomycin, and pactamycin) act synergistically with the K10 toxin in vivo (3,4). It would be desirable to also evaluate these compounds in vitro, using the thymocyte system described here.…”
Section: Days Fig 3 Influence Of Thymocyte-mycoplasma In-mentioning
confidence: 99%
“…These responses included lethargy, anorexia, diar-rhea, matted eyes, thymic involution, hepatocellular necrosis, and accumulations of leukocytes in alvec1ar septae [1,2]. In addition, mice could be sensitized to lethal toxicity and endotoxic shock by actinomycin D [2] and other antitumor drugs (e.g., pactamycin [9,10]) that display synergism with endotoxins but not with exotoxins.…”
Section: Discussionmentioning
confidence: 99%